Dampak Perubahan Iklim Terhadap Pola Hujan Dikhususkan Bagi Pertanian Di Pulau Sumatera Dan Kalimantan - Wanny K. Adidarma; Lanny Martawati; Syofyan D. M.K; Levina; Oky Subrata (Jurnal Teknik Hidraulik, 2010)
Identification of climate change impact to the rainfall pattern in Sumatera and Kalimantan becomes interesting because of its climate variability and nonclimate prediction zone if compared with Java which has only one type of climate with nonclimate prediction zone that can be neglected. The limited availability of rainfall data causes the approach leads to analyze average rainfall duration in certain threshold. The determination of rainfall duration boundary is based on the Oldeman climate classification for crop and second crop, i.e. 100200 mm. Analysis of the trend of average rainfall duration in various thresholds, indicates correlation between length and climate pattern. If compared to the equatorial pattern, the monsoon climate can be classified as robust toward climate change, although the wet season length is much shorter. In equatorial areas, change of rainfall duration is clearly detected and generally showing a negative trend or a longer dry season.